Identifying potential candidate Culicoides spp. for the study of interactions with Candidatus Cardinium hertigii. Issue 3 (6th May 2021) - Pilgrim, J.; Siozios, S.; Baylis, M.; Venter, G.; Garros, C.; Hurst, G. D. D.
Abstract: Culicoides biting midges (Diptera: Ceratopogonidae) are vectors responsible for the transmission of several viruses of veterinary importance. Previous screens of Culicoides have described the presence of the endosymbiont Candidatus Cardinium hertigii (Bacteroidetes). However, any impacts of this microbe on vectorial capacity, akin to those conferred by Wolbachia in mosquitoes, are yet to be uncovered and await a suitable system to study Cardinium ‐midge interactions. To identify potential candidate species to investigate these interactions, accurate knowledge of the distribution of the endosymbiont within Culicoides populations is needed. We used conventional and nested PCR assays to screen Cardinium infection in 337 individuals of 25 Culicoides species from both Palearctic and Afrotropical regions. Infections were observed in several vector species including C. imicola and the Pulicaris complex ( C. pulicaris, C. bysta, C. newsteadi and C. punctatus ) with varying prevalence. Phylogenetic analysis based on the Gyrase B gene grouped all new isolates within 'group C' of the genus, a clade that has to date been exclusively described in Culicoides . Through a comparison of our results with previous screens, we suggest C. imicola and C. sonorensis represent good candidates for onward study of Cardinium‐ midge interactions. Abstract : A nested PCR screen of 25 Culicoides species revealed Cardinium infections in the vector species C. imicola and the Pulicaris complex (e.g., C. bysta, C. newsteadi and C. punctatus ). Phylogenetic analysis based on the Gyrase B gene grouped all new isolates within 'group C' of the genus, a clade that has to date been exclusively described in Culicoides . The major vector species C. imicola and C. sonorensis represent the most viable species for further investigation of Cardinium ‐midge interactions.